Implementasi Smart Tracking Pada Manajemen Pengiriman Barang Berbasis Web - Udmah, Lailatul; Santoso, Firman (Universitas Muhammadiyah Riau, 2024)
Information technology today is in great need in various fields to facilitate business processes in companies and organizations. One of the areas that continues to grow in Indonesia is freight delivery. Delivery of goods by IKSASS Pondok Pesantren Salafiyah Syafi’iyah Sukorejo is usually done once a month, with delivery times varying for each rayon. This process of delivery is still done in writing, where all the processes, from entering data to searching and storing data using books, are time-consuming and risk loss of data or exchange of goods. The delivery management of the goods available at the Rayon IKSASS Banyuwangi in each sub is different, both in terms of operating costs and exit costs per sub, cash in sub, as well as other management methods. To solve the problem, the SDLC (Software Development Life Cycle) method was implemented using the PHP programming language and MySQL database. With the implementation of delivery management information systems, these differences can be managed more effectively, enabling more accurate and transparent monitoring of operating costs as well as facilitating financial and cash management in each sub rayon. The new system helps IKSASS managers perform delivery-related tasks, minimizes the risk of data loss, and speeds up the work process. In addition, the custodian can request the pickup of the goods without having to take them to the sub rayon iksass kalibaru office, as well as monitor the status of the delivery process until the arrival at the reception. Research results show that the implementation of Smart Tracking on this web-based delivery management is highly effective in improving the efficiency and accuracy of delivery processes.